Influence of the Lanthanide(Iii) Ion in {[Cu3ln2(Oda)6(H2o)6]•Nh2o}N (Lniii: La, Gd, Yb) Catalysts on the Heterogeneous Oxidation of Olefins - Aliaga-Vidal, C; Aliaga-Vidal, C; Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2017)
{[Cu3Ln2(oda)6(H2O)6]•nH2O}n (LnIII: La, Gd, Yb; odaH2: oxydiacetic acid) are reported as reusable heterogeneous catalysts in the oxidation of olefins. An influence of the LnIII ion on the catalytic performance of the series is observed, where the YbIII based framework presents a larger activity. The mentioned heteronuclear species are catalytically more active than the corresponding homonuclear catalyst {[Cu(oda)2]•0.5H2O}n. The use of t-butyl hydroperoxide (TBHP) as an oxidant gave conversions between 73-63% for styrene oxidation and between 57-48% for cyclohexene in dichloroethane/water (DCE/H2O). In four cycles, the loss of catalytic activity was less than 10%. Experimental data permit the consideration of the redox active CuII centres as the initiators of radical species generated from TBHP, which are responsible for the oxidation process of the studied olefins. Electron paramagnetic resonance (EPR) spectra of the reaction solutions, obtained in the presence of the spin trap PBN (N-tert-butyl-α-phenylnitrone), corroborate radical species formation during the oxidation process. DFT calculations support an electronic influence of the LnIII ions on the reactivity of the CuII centre, associated with changes in the stabilization of the empty CuII 3dx2 -y2 orbital, affecting the reduction of CuII with TBHP to CuI. Model calculations employing several density functionals support a higher electron affinity in the CuGdMOF system in comparison to CuLaMOF. In this way, electronic structure calculations agree with the interesting observed trend of the influence of the secondary metal centre (LnIII ions) on the properties of the active centre (CuII). © The Royal Society of Chemistry 2017.